Democratic innovations in Central and Eastern Europe: expanding the research agenda. Issue 1 (1st January 2019) - Gherghina, Sergiu; Ekman, Joakim; Podolian, Olena
ABSTRACT: Democratic innovations have recently gained momentum throughout the world. An increasing number of such practices takes place and coincides with a visible grow in the number of analyses focusing on the forms, functioning and effects of democratic innovations. In spite of these developments, a great deal of research on democratic innovations have largely neglected Central and Eastern Europe. This special issue of Contemporary Politics adds to the existing literature on democratic innovations by focusing on such attempts to deepen citizen participation in the political decision-making process in Central and Eastern Europe. Its attempt to expand the research agenda relies on new empirical evidence relative to three major forms of democratic innovations (direct democracy, deliberative democracy and citizens' involvement with the aid of ICTs).